A novel method for the risk assessment of human evacuation from cruise ships in maritime transportation. (February 2023) - Wang, Xinjian; Xia, Guoqing; Zhao, Jian; Wang, Jin; Yang, Zaili; Loughney, Sean; Fang, Siming; Zhang, Shukai; Xing, Yongheng; Liu, Zhengjiang
Highlights: A new method to identify hazards and quantify the associated risks of HEPS. A new cruise ship evacuation risk assessment model combining FMEA, BBN, ER approaches holistically. New investigation on the incorporation of a HSEO framework into the risk assessment of HEPS. Real case study and analysis of a large-scale evacuation drill of a cruise ship. Abstract: In maritime transport, evacuation, escape and rescue play a crucial role in protecting people's lives when a passenger ship is involved in a serious accident. The study aims to develop a new method to identify hazards, quantify and rank the associated risks in the process of Human Evacuation from Passenger Ships (HEPS). Firstly, based on extensive literature review and marine accident investigation reports, the risk factors affecting passenger ship evacuation were analysed and identified, and an analysis framework based on Human, Ship, Environment and Organization (HSEO) for HEPS was proposed. Secondly, a risk assessment model was proposed to quantify and rank risk factors in the process of HEPS. Finally, a large-scale evacuation drill of a cruise ship was taken as a case study to demonstrate the applicability of the proposed evaluation model, and accuracy of the results. The results reveal that (1) evacuation decision, operation of Life-Saving Appliances (LSAs) are the main risks affecting the safety of HEPS; (2) the behaviours of passengers have a relatively lower risk priority; and (3) future HEPS research should focus on the development of a multi-attribute decision system to address the issue on when to evacuate and when to abandon a ship.